Presenting Signs and Symptoms of Pericardial Effusions in the Pediatric Emergency Department. Issue 4 (April 2019) - Cully, Matthew; Buckley, Jason R.; Pifko, Elysha; Titus, Olivia M.
Abstract : Objectives: The primary objective of this study was to describe the frequency of the most common presenting signs and symptoms of pericardial effusions, particularly with relation to the size of the effusion. The secondary objective was to review the final etiology of the pericardial effusion in those patients who had presented to a tertiary care pediatric emergency department. Methods: This was a retrospective chart review of patients younger than 17 years who presented and were evaluated at the pediatric emergency department and subsequently diagnosed with a pericardial effusion during a period of 10 years. Results: A total of 23 patients matched the inclusion criteria. The most common symptom was shortness of breath (65%), followed by fever (52%), fatigue (44%), and chest pain (44%). Shortness of breath (60%) and chest pain (60%) were the most frequent symptoms among patients with a small pericardial effusion. Fever (86%), cough (71%), and shortness of breath (71%) were the most frequent symptoms among patients with moderate pericardial effusion. In patients with large pericardial effusions, the most frequent symptoms were shortness of breath (63%) and abdominal pain (63%). Tachycardia (52%) and tachypnea (52%) were the most common abnormal vital signs. The most common etiology was cardiac (44%) and autoimmune disease (26%). Conclusions: This study suggests that the presence of certain symptoms should be associated with a high index of suspicion for pericardial effusion for the pediatric emergency care physician.